(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Lower eyelid ectropion is a relatively common complication following cosmetic lower blepharoplasty, leading to impaired ocular surface protection and significant aesthetic and psychological consequences. The condition is frequently associated with lateral canthal tendon laxity, anterior lamellar deficiency, or cicatricial contracture, thereby necessitating individualized reconstructive strategies tailored to the underlying pathophysiology. Objective: To evaluate the surgical outcomes of lateral canthal tendon shortening, performed alone or in combination with full-thickness skin grafting or superficial temporal fascia grafting, in the management of postoperative lower eyelid ectropion following cosmetic surgery. Methods: This case series included three patients presenting with postoperative lower eyelid ectropion. Patients were treated with lateral canthal tendon shortening either as a standalone procedure or combined with full-thickness skin grafting or superficial temporal fascia grafting when indicated. Outcomes were assessed using marginal reflex distance 2 (MRD2), lower eyelid distraction and snap-back tests, corneal surface status, and subjective aesthetic evaluation over a 3-month follow-up period. Results: At 3 months postoperatively, the mean MRD2 significantly decreased from 8.7 ± 0.9 mm preoperatively to 4.0 ± 0.2 mm (p < 0.01). The lower eyelid distraction test improved from 10.0 ± 1.6 mm to 4.3 ± 0.3 mm, while the snap-back test converted from markedly positive (++/+++) to negative in all cases. All patients achieved a “good” aesthetic outcome, with complete resolution of ocular surface symptoms and no recurrence or postoperative complications observed during follow-up. Conclusions: Lateral canthal tendon shortening is a safe and effective surgical technique for the management of lower eyelid ectropion following cosmetic surgery. The procedure demonstrates high versatility and may be combined with full-thickness skin grafting or superficial temporal fascia grafting in cases involving complex anterior lamellar deficiency or recurrent ectropion. Larger-scale studies with extended follow-up durations are warranted to further validate the long-term efficacy and stability of this approach.